A apercepção virtual: um gênero de cognição extrassensorial na filosofia de Henri Bergson - Praciano, Ronney César Ferreira (2024)
This work considers that the relationship between the philosophy of Henri Bergson (1859-1941) and psychic research entails relevant theoretical consequences, which go beyond mere intellectual curiosity. Therefore, it is postulated here that some Bergsonian theses indicate a path through which it becomes viable to establish the existence of telepathy and clairvoyance as possible or even real phenomena, and, thus, begin to more systematically reconcile psychic research with Bergsonism. Our first chapter consists of showing the relationships between Bergson and psychic research, revealing that the philosopher's interest in these subjects highlights their theoretical importance for Bergsonism; As a consequence, we extracted from this first analysis an important notion for the explanation of telepathic phenomena, namely, that of a “psychic endosmosis” between consciousnesses, which would indicate the existence of a virtual field of unconscious perceptions, although capable of being perceived. In our second chapter, we tried to show how current perception is obtained from a general and broader perception (perception or virtual field) that extends to all reality, having been diminished by the role of sensorimotor devices. Because they act as reducing filters of conscious perception, instead of producing it, nothing would prevent a consciousness from recovering something from the extent to which it was diminished, and this precisely because it transcends the common sensory activity that delimits it. In the third and final chapter, we consider that the virtual field of perceptions results from the activity of the Supraconsciousness which, by temporally linking all individual consciousnesses and nature as a whole, enables, in turn, the phenomenon of clairvoyance. Consideration of these phenomena would endorse the ontological thesis of a virtual and all-embracing psychic field, maintained by the activity of Supraconsciousness. When being, so to speak, “invaded” by the latter, individual consciousness would perceive virtual images coming from everywhere, and this precisely because it consists of an extra- spatial psychic phenomenon, that is, of a purely temporal nature, and which goes back, moreover, to the recovery of unconscious vital instincts. Thus, our thesis consists precisely in stating that there is a sui generis form of perception not thematized in Bergson's philosophy, virtual apperception, which is a form of extrasensory access to the real, of which the psychic phenomena of telepathy and clairvoyance would be specific manifestations. It is therefore concluded that psychic phenomena are relevant to bergsonism, as they allow us to extract from the latter – in an attempt to explain the former – a non-explicit form of access to the real, characterized by a virtual “apprehension” of processes coinciding in time.